Mechanical traits of fine roots as a function of topology and anatomy. (26th May 2018) - Mao, Zhun; Wang, Yan; McCormack, M Luke; Rowe, Nick; Deng, Xiaobao; Yang, Xiaodong; Xia, Shangwen; Nespoulous, Jérôme; Sidle, Roy C; Guo, Dali; Stokes, Alexia
Abstract: Background and Aims: Root mechanical traits, including tensile strength ( T r ), tensile strain ( ε r ) and modulus of elasticity ( E r ), are key functional traits that help characterize plant anchorage and the physical contribution of vegetation to landslides and erosion. The variability in these traits is high among tree fine roots and is poorly understood. Here, we explore the variation in root mechanical traits as well as their underlying links with morphological (diameter), architectural (topological order) and anatomical (stele and cortex sizes) traits. Methods: We investigated the four tropical tree species Pometia tomentosa, Barringtonia fusicarpa, Baccaurea ramiflora and Pittosporopsis kerrii in Xishuangbanna, Yunnan, China. For each species, we excavated intact, fresh, fine roots and measured mechanical and anatomical traits for each branching order. Key Results: Mechanical traits varied enormously among the four species within a narrow range of diameters (<2 mm): <0.1–65 MPa for T r, 4–1135 MPa for E r and 0.4–37 % for ε r . Across species, T r and E r were strongly correlated with stele area ratio, which was also better correlated with topological order than with root diameter, especially at interspecific levels. Conclusions: Root topological order plays an important role in explaining variability in fine-root mechanical traits due to its reflection of root tissue development. Accounting for topological order when measuring fine-root traits therefore leads to greater empirical understanding of plant functions (e.g. anchorage) within and across species.